2008
DOI: 10.1111/j.1526-4637.2008.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Self-Management Strategies to Reduce Pain and Improve Function among Older Adults in Community Settings: A Review of the Evidence

Abstract: Our results suggest that a broad range of self-management programs may provide benefits for older adults with chronic pain. Research is needed to establish the efficacy of the programs in diverse age and ethnic groups of older adults and identify strategies that maximize program reach, retention, and methods to ensure continued use of the strategies over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(65 citation statements)
references
References 83 publications
2
63
0
Order By: Relevance
“…The high cost and adverse side effect profiles associated with many analgesic treatments, as well as the potential for drug-drug interactions, operate as significant barriers to the use of standard pharmacologic treatments in older adults [19,74]. Based on studies conducted to date, combined pharmacologic and non-pharmacologic therapies give the best results for pain relief.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high cost and adverse side effect profiles associated with many analgesic treatments, as well as the potential for drug-drug interactions, operate as significant barriers to the use of standard pharmacologic treatments in older adults [19,74]. Based on studies conducted to date, combined pharmacologic and non-pharmacologic therapies give the best results for pain relief.…”
Section: Resultsmentioning
confidence: 99%
“…Reid et al suggested in their review (N = 27) that a broad range of self-management programs (yoga, massage therapy, TC, and music therapy) may provide benefits for older adults with CMP highlighting the need for research to establish the efficacy of the programs in different age and ethnic groups of older adults and identify strategies that maximize program reach longterm participation [74].…”
Section: Mind-body Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a literature review, Reid et al [6] investigated the evidence on self-managed interventions for pain among older adults. A total of 27 articles were identified, including those that evaluated programs sponsored by the Arthritis Foundation and other programs such as yoga, massage therapy, Tai Chi, and music therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The ICPI was well received by participants and demonstrated positive outcomes in this preliminary study. Further research with more participants is feasible and While research has established the effectiveness of these therapies, delivered via traditional face-toface methods, for those with chronic pain (Broderick et al, 2014;Hoffman, Papas, Chatkoff, & Kerns, 2007;LeFort, Gray-Donald, Rowat, & Jeans, 1998;McCracken, MacKichan, & Eccleston, 2007;Nicholas et al, 2010;Reid et al, 2008;Sveinsdottir, Eriksen, & Reme, 2012), early studies documenting delivery of these therapies online involved individuals with depression, anxiety, other social and mood disorders (Andersson, 2006;Andersson, Bergstrom, Carlbring, & Lindefors, 2005;, and other chronic diseases (Ghahari, Packer, & Passmore, 2009;Kerr et al, 2010;Lorig, Ritter, Laurent, & Plant, 2006). The effect of an Internet-based chronic pain psycho-educational intervention that included selfmanagement and CBT had not been studied in depth prior to initiation of this project.…”
mentioning
confidence: 97%